Humanizing cities through car-free city development and transformation - Doheim, Rahma M. 1976-; Farag, Alshimaa Aboelmakarem 1979-; Kamel, Ehab 1975- (IGI Global, 2020)
"This book explores the concepts of car-free cities and city humanization as possible solutions to reduce the deteriorating effect on the environment and the community. The publication discusses the urban initiative to implement pedestrianization and humanization of cities and public spaces to promote the concept of car-free living"--